HISTOARCHITECTURE, SEASONAL VARIATION AND REPRODUCTIVE FUNCTION OF THE NEUROENDOCRINE ORGAN, BRAIN OF FRESHWATER PRAWN, MACROBRACHIUM GANGETICUM - Gupta, Akhilesh Kumar; Roy, D. (Journal of Indian Fisheries Association, 2010)
Histoarchitecture, seasonal variation and reproductive function of the neuroendocrine structure, brain of freshwater prawn Macrobrachium gangeticum were studied. Three types of NSCs- ‘B’, ‘C’ and ‘D’ were found to be concentrated in four groups in brain. These cells showed larger diameters and higher activity during breeding season. In case of females, the ‘C’ cells were more active during vitellogenic period. Brain extracts were found to induce gonadal maturation of both males and females. Key words: Macrobrachium gangeticum, Brain, Neurosecreory cell, Gonads.